Drying of olive leaves in a geothermal dryer and determination of quality parameters of dried product. (March 2019) - Helvaci, H.U.; Menon, A.; Aydemir, L.Y.; Korel, F.; Akkurt, G.G.
Abstract: In this study, a cabinet type geothermal dryer was designed, operated and tested for drying olive leaves with minimum losses of phenolic content and antioxidant capacity by optimization of drying conditions. Two factors; face centered central composite design was applied and response surface methodology was used to optimize the drying conditions of olive leaves. The results indicate that phenolic content stability were mainly affected by air temperature, whereas antioxidant capacity is affected by both air temperature and velocity (p<0.05). The optimal drying conditions were found to be at 50°C of air temperature and 1 m/s of air velocity for the minimum losses of determined quality parameters, where 88.8% of phenolic content and 95.3% of antioxidant capacity were recovered.